2010
DOI: 10.1017/s0033291710001996
|View full text |Cite
|
Sign up to set email alerts
|

P300 deficits in adults with attention deficit hyperactivity disorder: a meta-analysis

Abstract: To our knowledge, this is the first meta-analysis of P3 characteristics in adults with ADHD. It reveals a significantly decreased P3 amplitude during target detection. Our result that the reduction in P3 amplitude increases with age is interpreted in a neurodevelopmental context.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
64
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 106 publications
(76 citation statements)
references
References 66 publications
9
64
3
Order By: Relevance
“…Average waveforms were examined at the midline electrodes Fz, Cz, and Pz and are illustrated in Figure 1. Consistent with previous studies (see Szuromi, Czobor, Komlosi, & Bitter, 2011 for review) amplitude appeared maximal at the Pz site in the time window associated with P3b. The average response time for the entire sample was 509 ms ( SD = 55 ms).…”
Section: Methodssupporting
confidence: 92%
“…Average waveforms were examined at the midline electrodes Fz, Cz, and Pz and are illustrated in Figure 1. Consistent with previous studies (see Szuromi, Czobor, Komlosi, & Bitter, 2011 for review) amplitude appeared maximal at the Pz site in the time window associated with P3b. The average response time for the entire sample was 509 ms ( SD = 55 ms).…”
Section: Methodssupporting
confidence: 92%
“…In a visual Go/Nogo task, Prox et al (2007) compared the ERPs of adult ADHD patients and controls and found a tendentially decreased P300 at parietal electrode sites and a significantly enhanced subsequent slow wave in the time window from 600 to 800 in the frontal cortex in the ADHD group relative to controls. Similar results were found by a metaanalysis conducted by Szuromi et al (2010) that showed a significantly reduced P300 amplitude related to target detection in adult ADHD subjects compared to controls. Furthermore, Barry et al (2009) reported topographic differences between an AD/HD group and controls in the P300 to visual non-targets.…”
Section: Introductionsupporting
confidence: 88%
“…Regular P300 amplitudes are in contrast with the data from other studies (Szuromi et al, 2011;Woltering et al, 2013). However, most studies used Go/No-Go tasks (e.g., Wiersema et al, 2006) to measure response inhibition and are therefore difficult to compare.…”
Section: Discussionmentioning
confidence: 67%